ASSESSMENT OF THE VALUE OF A COMPANY: HISTORICAL AND THEORETICAL BASIS - Aktamov Bobirjon Mardon ugli (European Science Publishing, 2025)
Modern. economy under the circumstances every one company for every how method and tools through done increaseable financial - economic activity efficiency constant monitoring important importance has. Analytical point of view from the point of view such monitoring efficiency analysis certain method how correct selected and to be used related. Organization efficiency how much high if , external and internal users for necessary the information that is inside received effective information the company financial status and management different at the levels acceptance made of decisions efficiency so much reliable It will be.
Keywords: Expenses assessment; activity efficiency; financial status monitoring; cost approach; income approach; comparative approach; assessment method; business value; value maximum at the level increase; value factors.